2021
DOI: 10.1021/acsestengg.1c00188
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Peroxymonosulfate in TiO2-Mediated Photocatalytic Oxidation: Dependence of Kinetic Enhancement on Target Substrate and Surface Platinization

Abstract: An enhancing effect of peroxymonosulfate (PMS) on photocatalytic activity has previously been demonstrated, but the research focus was concentrated primarily on the extent to which treatment efficiency was improved. To further comprehend the role of PMS, this study examined the TiO2 photocatalytic systems in the presence of PMS for the oxidation of diverse organics and showed that the extent of performance enhancement via PMS addition was substrate-dependent. This resulted from the involvement of multiple oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Moreover, the TC degradation experiments with D 2 O acting as the solvent also verified the existence of 1 O 2 (Figure S12). The results of EPR with DMPO serving as spin traps revealed the existence of O 2 –• in CoSi and MnCoSi/PMS systems (Figure c). , Moreover, the characteristic signals of SO 4 –• , • OH, and 1 O 2 could be observed in both MnCoSi/PMS and CoSi/PMS systems (Figure d,e). As shown in Figure S13, the addition of PMS and TC made the current drop slightly, indicating that there was no electron transfer path in the system . When PMSO was added, the degradation of TC was almost unaffected, which ruled out the contribution of high-valent metal species (Figure S14).…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, the TC degradation experiments with D 2 O acting as the solvent also verified the existence of 1 O 2 (Figure S12). The results of EPR with DMPO serving as spin traps revealed the existence of O 2 –• in CoSi and MnCoSi/PMS systems (Figure c). , Moreover, the characteristic signals of SO 4 –• , • OH, and 1 O 2 could be observed in both MnCoSi/PMS and CoSi/PMS systems (Figure d,e). As shown in Figure S13, the addition of PMS and TC made the current drop slightly, indicating that there was no electron transfer path in the system . When PMSO was added, the degradation of TC was almost unaffected, which ruled out the contribution of high-valent metal species (Figure S14).…”
Section: Resultsmentioning
confidence: 93%
“…As a result, the metal dopant transports electrons and holes created by the light beam to the reaction surface, preventing their recombination rate and thus enhancing photodegradation. A pseudo-first-order kinetic equation can be used to calculate the apparent rate constant of kinetic degradation for samples with different concentrations. , The investigation showed that the rate constants are calculated to be 0.00413, 0.0097, 0.0226, 0.06, and 0.07442 min –1 for MoS 2 , 5% Mn-doped MoS 2 , 10% Mn-doped MoS 2 , 15% Mn-doped MoS 2 , and 20% Mn-doped MoS 2 , respectively (shown in Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the as-synthesized MoS 2 catalysts can be readily used for catalytic applications without further processing. 55,56 However, the ferromagnetism of a MoS 2 system is induced by vacancy, deformation, or zigzag edges. 57 SI Figure S4a,4b present the magnetization curves (M-H) of the MoS 2 nanoflowers and nanosheets respectively measured at ambient temperatures (∼300 K).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The study shows that the atomic ratio of the Mo:S changed from 1:1.189 to 1:1.975, implying direct evidence that the number of unsaturated sulfur atoms when the structure changed from nanosheets to nanoflowers. , This is possible for two reasons (1) formation of few-nanometer MoS 2 nanoflowers having ultrathin sharp edges (2) usage of CH 3 CSNH 2 as a precursor may enhance the number of unsaturated sulfur atoms at the exposed edge during synthesis. Thus, the as-synthesized MoS 2 catalysts can be readily used for catalytic applications without further processing. , …”
Section: Resultsmentioning
confidence: 99%